La structuration textuelle en discours scientifique : comparaison oral / écrit - Jacques, Marie-Paule (CHIMERA: Revista de Corpus de Lenguas Romances y Estudios Lingüísticos, 2017)
This paper focuses on the organisation of scientific presentations, by comparing their written and oral form. Taking as my point of departure the conventional IMRAD structure (Introduction – Material and Methods – Results And Discussion), I first analyse the research articles of the French scientific corpus of the EIIDA project, which comprises 15 articles from the field of organic geochemistry. They do not totally follow the IMRAD structure, frequently including a section that explains the geographical context of the research and often conflating or transforming other sections. The conference presentations move further away from IMRAD, giving even more room to the geographical context and often reducing the Methods section to just one word. Both written and oral presentations provide the readers/audience with little or no guidance to the macrostructure. In the written articles, the headings that segment the text fulfill this function, simultaneously providing the reader with an architecture and landmarks. The oral presentations generally provide no counterpart for this visual organisation and adopt a more narrative form. Keywords:Discourse organization, headings, IMRAD structure